A pedagogical framework for facilitating parents' learning in nurse–parent partnership. Issue 2 (17th September 2017) - Hopwood, Nick; Clerke, Teena; Nguyen, Anne
Abstract : Nursing work increasingly demands forms of expertise that complement specialist knowledge. In child and family nursing, this need arises when nurses work in partnership with parents of young children at risk. Partnership means working with parents in respectful, negotiated and empowering ways. Existing partnership literature emphasises communicative and relational skills, but this paper focuses on nurses' capacities to facilitate parents' learning. Referring to data from home visiting, day‐stay and specialist toddler clinic services in Sydney, a pedagogical framework is presented. Analysis shows how nurses notice aspects of children, parents and parent–child interactions as a catalyst for building on parents' strengths, enhancing guided chance or challenging unhelpful constructs. Prior research shows the latter can be a sticking point in partnership, but this paper reveals diverse ways in which challenges are folded into learning process that position parents as agents of positive change. Noticing is dependent on embodied and communicative expertise, conceptualised in terms of sensory and reported channels. The framework offers a new view of partnership as mind‐expanding for the parent and specifies the nurse's role in facilitating this process.